Musra Dahrizal Katik Rajo Mangkuto : Tokoh Budayawan dan Seniman Tradisional Minangkabau (1963-2014) - Arisman, Richi - (Pendidikan Sejarah, 2014)
This thesis examines the Musra Dahrizal Katik Rajo Mangkuto (Mak Katik) : People OfMinangkabau Cultural and Traditional Artist (1963-2014). Writing a biography of Mak Katikmore emphasis on activity and creativity as an artist and humansist. As a humanist and artist, henot only never invited in the country but are also able to take him to get involved in promotingculture and traditional artist Minangkabau National and International level. This study needs to bedone because it can be seen how or work done in preserving Mak Katik traditional Minangkabauculture as well as to facilitate this research, the authors the problem as follows : how backgroundlifeâs Mak Katik, Mak Katik initial interest to the study of traditional Minangkabau culture, howthe role of fiddling, as a cultural and traditional Minangkabau artist, how the views of Mak Katikof awareness about indigenous people today and the latter of which is to be examined are thecommunity perceptions of Mak Katik. Method that be used in this research is method thatappropriate with history research which follow some steps like : (1) Heuristic, (2) Source Critic,(3) Analysis and Interpretation, (4) Historiography.Based on the research that has been done canconcluded that : a side from looking at the efforts made Mak Katik as cultural leaders andtraditional artist Minangkabau, i also conduct research on the lifeâs history Mak Katik from earlychilhood through to get married.